Development of a Training Program for Upskilling Science Teachers’ Laboratory Competence - Cabacungan, Mark Vincent R.; Calzada, Marc Paul T. (Future Science / FSH-PH Publications, 2025)
Science education in the Philippines is presently alarming due to the low achievement rating in various international assessments. This problem is rooted in the low utilization of laboratory-based instruction due to inadequate laboratory facilities and equip-ment. Hence, a descriptive-correlational research approach was conducted to determine the knowledge and skill competence of public-school teachers. Using a researcher-made survey ques-tionnaire, it was revealed that the respondents have very high knowledge and skill competence when it comes to laboratory instruction with a mean score of 4.08 apiece. Meanwhile, an R-value of 0.9121 was computed showing a positive relationship between knowledge and skill competence. The result shows that teachers are competent enough to perform lab-based activities; however, there is a need for them to undergo training and semi-nars due to the low utilization of lab activities. From here, a training program dubbed as SCILAW was formulated. Through this, teachers will be able to hone their knowledge and skills in using lab-based teaching approaches.